To solve the quadratic equation \(49x^2 = -392x - 784\) using the perfect square trinomial pattern, we can first rearrange the equation to standard form:
\[ 49x^2 + 392x + 784 = 0 \]
Next, we divide the entire equation by \(49\) to simplify it:
\[ x^2 + 8x + 16 = 0 \]
Now we notice that \(x^2 + 8x + 16\) can be factored as a perfect square trinomial:
\[ (x + 4)^2 = 0 \]
Taking the square root of both sides gives us:
\[ x + 4 = 0 \]
Solving for \(x\):
\[ x = -4 \]
Thus, the solution to the quadratic equation is:
\[ \boxed{-4} \]